Cause and analysis of hydraulic pump failure. Issue 2 (April 2021) - Shang, Li; Wang, Na
Abstract: After a period of use, the internal parts of the hydraulic pump will be worn one after another, resulting in the reduction of the movement efficiency of the hydraulic pump and various problems. Usually, this is a sign of damage to the hydraulic pump. If the hydraulic pump is seriously damaged and beyond the scope of repairable technology, it should be replaced in time and repaired effectively. If it is difficult to repair, replace the parts if necessary to improve the working efficiency of the hydraulic pump. Under certain circumstances, experienced maintenance personnel can fully improve the working efficiency of hydraulic pump through precise maintenance and effective matching.